Use of industry 4.0 technologies in worker safety and health: a systematic literature review - Silva, Caroline Martirena Monks da; Silva, Marco Antonio Garcez da; Pereira, Aline Soares; Franz, Luis Antonio dos Santos; Bemvenuti, Renata Heidtmann (Brazilian Journal of Production Engineering, 2021)
According to data from the Digital Occupational Health and Safety Observatory, since 2012, Brazil has recorded more than 17 thousand deaths and 4.5 million work accidents, with accidental leaves being more frequent (65%) than due to illness (35%). Understanding the great challenge that this represents for productivity, economy and quality within corporations, there are approaches using industry 4.0 technologies for the prevention of work accidents. The objective of this work was to carry out a systematic review on the use of Industry 4.0 technologies applied to Occupational Health and Safety for the prevention of work accidents. A systematic literature review was carried out using the Methodi Ordinatio, with the inclusion of scientific articles published in databases Science Direct, Scopus and Web of Science. Search terms were used: “Industry 4.0”; “Occupational Health”; and “Safety”; using the Boolean AND operator. 99 documents were found, remaining 94 after the elimination of duplicate articles and 19 were selected for analysis and thorough reading. Were considered promising the possibilities of preventive and simultaneous occupational management using industry 4.0 technologies. Literature reflects the importance of technological adaptations in terms of Occupational Health and Safety management in Brazil, to make it more propositional, practical, simultaneous, and efficient.